Mechanism and Evolution Control of Wide Coal Pillar Bursts in Multithick Key Strata - Wenhao Guo; Anye Cao; Chengchun Xue; Yang Hu; Songwei Wang; Qian Zhao (Shock and Vibration)
Coal mine pillar burst frequently occurs in Western China, which seriously restricts safe production. This paper takes the 35 m coal pillar of the 3102 working face of MKQ coal mine as the engineering background. The mechanism and evolution control of pillar bursts in multithick key strata are studied using field investigation, theoretical analysis, and numerical simulation. The mechanism of dynamic and static stress-induced pillar bursts was revealed combining the “O-X” broken features for key strata and numerical simulation of pillar stress evolution. A prevention scheme is put forward for strata presplit blasting and adjusting coal pillar width to minimize the dynamic and static stresses. The results demonstrate the following. (1) In the multithick strata, the first and second near-field subkey strata have perpendicular “O-X” broken features, whereas the third far-field subkey has parallel “O-X” broken features. The working face has three kinds of periodic weighting phenomena: long, medium, and short. (2) The simulated vertical stress curve of 35 m coal pillar goes through three states: two-peak, asymmetric trapezoidal and symmetrical trapezoidal shape with the different advancing position of working face. The stress concentration is extensively promoting a high-risk area for rock burst. (3) The coal pillar burst was induced by the superposition of energy released by the key strata breaking and the elastic energy accumulated in the wide coal pillar. (4) The monitoring data showed that the long, medium, and short periodic weighting steps of multithick key strata are 141.6 m, 43.2–49.6 m, and 17.6–27.2 m, respectively. The microseismic events energy, frequency, and stress of hydraulic support increment are the highest during the long periodic weighting, and the spatial distribution of microseismic events coincides with the stress concentration area. The theoretical analysis is confirmed with the field practice.